2004
DOI: 10.1042/bj20040046
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of the deoxyribonuclease 1 gene: lessons from the Dnase1 knockout mouse

Abstract: The tissue distribution of deoxyribonuclease 1 (DNASE1, DNase I), a Ca2+ and Mg2+/Mn2+-dependent secretory endonuclease, has previously been investigated. However, most of these studies did not account for the existence of different members of the DNASE1 gene family, did not differentiate between endogenous DNASE1 protein synthesis and its extracellular occurrence or were not performed with methods allowing both a sensitive and a specific detection. Now we re-examined the DNASE1 gene expression pattern by taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 43 publications
4
81
0
Order By: Relevance
“…19 Serum Dnase1 activity was quantified using the single radial enzyme diffusion assay and the native polyacrylamide gel electrophoresis zymogram technique as previously described. 11,12 Immunoblotting. Immunoblotting was performed on liver homogenates prepared as described above for quantitative DNA fragmentation assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Serum Dnase1 activity was quantified using the single radial enzyme diffusion assay and the native polyacrylamide gel electrophoresis zymogram technique as previously described. 11,12 Immunoblotting. Immunoblotting was performed on liver homogenates prepared as described above for quantitative DNA fragmentation assay.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 DNASE1 gene expression has been demonstrated in a number of different organs of the urogenital and alimentary tracts as well as in the murine liver. 11 In a previous report, we showed that Dnase1 deficiency in the mouse promotes anti-DNA autoimmunity, suggesting a protective role of Dnase1 through its ability to degrade chromatin presumably liberated during cell death. 12 In addition, we have demonstrated that extracellular DNASE1 diffuses into necrotic cells, and together with the plasminogen system facilitates necrotic chromatin breakdown in vitro.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the kidney, DNase I is highly expressed (18,40). We showed recently that among other endonucleases, EndoG and DNase II are also highly expressed in the kidney, whereas the expression of caspase-activated DNase and DNase ␥ is very low (17).…”
Section: Discussionmentioning
confidence: 99%
“…However the actual role of the cytotoxic endonucleases was clarified much later. Cytotoxic endonucleases were found in all studied cells and tissues, including the prostate (Koizumi, 1995;Napirei et al, 2004). The enzymes belong to the family of hydrolyses that cleave phosphodiether bonds in DNA.…”
Section: Cytotoxic Endonucleases In Normal Prostate and Prostate Cancmentioning
confidence: 99%